Empowerment of Educational Organizations in the Perspective of the Balanced Score Card (BSc) as an Alternative to Measuring the Performance of Educational Institutions - Ermawati, Ermawati; Ali, Makhrus; Yasmadi, Bambang; Wahidin, Didin; S Mochtar, Hendi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Educational institutions can function well if their performance can be measured clearly. Educational institutions should be empowered towards optimal empowerment, by developing schools with strategic planning, a vision and mission, an independent school, empowering the community by many efforts to increase the role and participation of the community through school committees. To make schools as educational institutions of high quality, they need to be evaluated and controlled. The School achieved can be said that the institution is measurable. One alternative is offered in measuring the performance of schools known by the Balanced Scorecard (BSC). The Balanced Scorecard was introduced by Robert Kaplan and David Norton by understanding the school's mission and strategy into objectives and measures, which are arranged in four perspectives.